Optimalisasi Bandwidth Dengan Load Balancing Menggunakan Metode Peer Connection Classiffier di RT/RW NET Evolvet - Aminulloh, Ihsan; Rofiq, Mochammad (JURNAL SISTEM KOMPUTER ASIA, 2024)
RT/RW Net is a non-governmental computer network that covers the scope of RT or RW through wired or wireless 2.4 Ghz media and hotspots as a means of public communication which is freely accessible because it is not bound by laws and government bureaucracy, one of the RT/RW Net it is RT/RW Net Evolvet. Prior to load balancing on the RT.RW Net Evolvet network, which has 2 network ISPs. Initially only had 1 ISP connected to the proxy then channeled it into 1 cable output that led to the switch. However, using 1 ISP is not enough to meet the bandwidth that will be distributed to users, so RT/RW Net Evolvet wants to increase bandwidth by installing 1 more ISP. With 2 ISPs already installed, it will be used together not only using 1 ISP and channeled into 1 path towards the switch and if one ISP dies then network settings are needed so that the network can connect to the two ISPs in a way if one ISP dies then the network will automatically switch to an active ISP. Of the two internet services, RT/RW Net Evolvet wants to use all ISP services to be combined so that internet bandwidth is faster and more stable, and reduces the buildup of bandwidth or data traffic on 1 ISP which results in unstable and excessive bandwidth on the traffic line. One solution that can be used to maintain the quality of the internet connection by keeping the traffic running balanced and saving bandwidth is to divide the load or buildup of bandwidth traffic into several paths or links by using a load balancing technique using the PCC (Peer Connection Classiffier) ​​method. In the test, it is done by looking at the bandwidth traffic on the interface and looking at the firewall connection. From the trials that have been carried out, it indicates that the configuration that has been made on the proxy is successful and running according to the design. Make the network on RT/RW Net Evolvet stable and optimize network performance on RT/RW Net Evolvet.